Children’s representations of the COVID-19 lockdown and pandemic through drawings - Cornaggia, Alessia; Bianco, Federica; Gilli, Gabriella; Marchetti, Antonella; Massaro, Davide; Castelli, Ilaria (Frontiers in Psychology, 2022)
The Covid-19 pandemic and the measures to face it have placed children and their caregivers in front of many challenges that could represent sources of stress. This work aims to explore the point of view of children through drawing, as a spontaneous means of expression, relating it to parents' perceptions of children’s difficulties, strengths, and mentalization skills. The sample consists of 18 children (mean age = 8.22, SD = 1.79). Parents were asked to complete: a socio-demographic questionnaire with information on the impact of Covid-19 on the family, the Strengths and Difficulties Questionnaire, and the Everyday Mindreading Scale. Children were asked to draw three moments: "Before" the pandemic, "During" the lockdown, and "After", when the Covid-19 will be passed. The drawings were coded by constructing a content and expressive analysis grid, adapting coding systems found in the literature. Data were collected at the beginning of the summer of 2020, just after the first lockdown period (from March to May 2020 in Italy). The results of the present work are in line with previous studies that reported experiences of well-being and tranquility of children in time spent at home with family during the pandemic. From the drawings emerges that children feel sufficiently able to master the situation, as reflected by including themselves in drawings and providing many details of the house in "During" drawings. The literature also reports a feeling of sadness/loneliness caused by the lack of friends, an element that we also find in the tendency to represent friends significantly more in the drawings concerning the future. Some contents of drawings (inclusion of friends, relatives, and parents) appeared associated with emotional, interpersonal, and mentalizing abilities of children, as perceived by parents. Exploring children’s representations of a stressful event like the pandemic through drawings allows to focus both on their difficulties and on their resources, with useful implications for the educational support.